EFFECT OF TREATMENT SOLUTION ON THE MICROSTRUCTURE AND MICROHARDNESS OF TERNARY Ni-Al-Nb ALLOY DOPED WITH TITANIUM - Hikmat Nugraha; Pradoto Ambardi; Djoko Hadi Prajitno (Jurnal Sains Materi Indonesia, 2020)
EFFECT OF TREATMENT SOLUTION ON THE MICROSTRUCTURE AND MICROHARDNES OF TERNARY Ni-Al-Nb ALLOY DOPED WITH TITANIUM. Nickel-based superalloys have been widely used in various applications, which require high strength at high temperatures. Most types of these superalloys is age-hardenable because they have γ’ particles' chemical composition Ni3(Al, Ti) in γ’-phase matrix. This research will be used alloy Ni-Al-Nb added alloying elements Ti. This research was conducted to study the mechanical properties, microstructure conditions in some alloys Ni-Al-Nb added distinction Titanium element (0,5% and 1% Ti) using the method of aging temperature variation performed at a temperature of 650 °C,700 °C and 750 °C with a holding time 4 hours and air cooling. Tests were conducted to determine the characterization of the specimen includes testing metallographic optical microscope, Rockwell hardness C and SEM- EDS,XRD. Results obtained from this research that addition of titanium element affecting the hardness values as well as the results of the cast, solution treatment and aging process results. The 1% Titanium content can affect the gamma prime coarsening and make the grain on the microstructure result smooth.